The value of tawhid in Islamic studies: The foundational ideology of muhammadiyah education - Asri Asri; Lestari Lestari; Elihami Elihami; Musriani Musriani (Institute of Information Technology and Social Science (IITSS), 2025)
Faith-based education in Indonesia has long been rooted in the central principle of Tawhid—the oneness of God—which serves as the foundation of Islamic worldview and moral consciousness. This study explores how the value of Tawhid shapes the educational ideology of Muhammadiyah and influences teachers’ roles in promoting holistic learning. Guided by a mixed-methods research design, the study involved 200 teachers and students from Muhammadiyah schools and universities across South Sulawesi, Yogyakarta, and Central Java. Data were collected through survey questionnaires and semi-structured interviews, then analyzed using descriptive statistics and thematic coding. The findings revealed that teachers who internalize Tawhidic values demonstrate stronger ethical leadership, student-centered pedagogy, and an integrative approach between faith, knowledge, and service. Participants perceived that the embodiment of Tawhid in teaching not only nurtures students’ spiritual awareness but also enhances discipline, empathy, and a sense of responsibility toward the community. The study concludes that Tawhid serves as both the ideological and pedagogical foundation of Muhammadiyah education, guiding teachers to become moral exemplars and transformative educators. It recommends continuous professional development programs emphasizing Tawhid-based pedagogy to sustain Muhammadiyah’s mission of producing intellectually competent and spiritually grounded generations.